A collection and transcription of Ndandanda dance songs of Nkayi district - Mutusva, Mirriam (Midlands State University, 2020)
The purpose of this study was to collect Ndandanda dance songs for documentation for the benefit of future generations. In order to collect data on Ndandanda songs, an ethnographic research design in the qualitative form was employed. Participants were selected using the purposive and snowball sampling techniques. Data instruments such as participant observation and semi structured interviews were employed to collect the much needed data for this study. The songs that were collected and gathered from observation and interviews were transcribed and presented in the form of staff notation. Findings of the study revealed that Ndandanda dance songs are songs sung to accompany the Ndandanda dance. Ndandanda dance is a hunting dance prominent in Nkayi and parts of Midlands by the Ndebele people. The dance was performed by men who were believed to have the spirit of hunting (ubujimbi). The one possessed would be directed in the bush to kill an animal for family gatherings nowadays, it is performed for entertainment and as part of tradition by the Ndebele people of Nkayi. A total of ten songs were collected and transcribed. From the transcribed songs, I found out that they were performed under three contexts which are hunting, entertainment and for ritual ceremonies. The songs communicate norms and values of people in that society and they also ensure continued existence of the tradition and culture of the community. The songs also promote unity, sense of belonging and are a way of entertainment. The study therefore recommends that some Ndandanda songs be used in schools for teaching purposes so as to safeguard a people’s cultural heritage. Resource persons from the local community can be used to conduct workshops on the teaching of the songs including the dance itself. I also recommend that local schools and the district National Arts Council of Zimbabwe organize an annual festival on Ndandanda dance performances. I also recommend scholars to study the actual dance, how it is performed, instruments used, the drumming that accompany the singing, props used and other important aspects of the dance